The United Nations Office for the Coordination of Humanitarian Affairs (OCHA) Humanitarian Response Plan in Handling the Afghanistan Food Crisis - Dea Apriliyati; Etha Pasan (Papua Journal of Diplomacy and International Relations, 2024)
The food crisis experienced by Afghanistan constitutes a humanitarian crisis. The Government of Afghanistan alone cannot handle this severe shortage of food. Seeing the inability of government to manage the crisis, UN OCHA took initiatives by introducing Humanitarian Response Plan (HRP) programme. This article aims to analyse UN OCHA’s role and challenges dealing Afghanistan food crisis 2016-2022. Using the qualitative method with secondary data collections, the result shows that the role of UN OCHA in dealing with the Afghanistan food crisis had helped government of Afghanistan in a significant way despite facing serious challenges. The role of UN OCHA is channelled through HRP programme which contains food security and agriculture, nutrition, health, WASH, education, emergency shelter and NFI, protection, and coordination. Challenges in the distribution are influenced by aspects of access, adequacy, security and vulnerability, and sustainability. This article contributes the field of international relations, especially dealing with the issues of food scarcity. It also hopes to increase interests among scholars to study food crisis and can offer input for UN OCHA to improve quality and quantity of humanitarian assistance. KEYWORDS Humanitarian Response Plan; Food Crisis; UN OCHA